Health Risk Assessment of Physical and Chemical Hazards in the Painting Area of a Manufacturing Company - Aulia Indar Ayuningtyas; Sjahrul Meizar Nasri (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: The work process of the Painting Area in a Manufacturing Company can pose a risk to physical and chemical health hazards for workers. Hazard analysis and identification, exposure assessment, and risk assessment  are, therefore, needed to protect the health of workers from these health hazards, which can later be used as a basis to determine appropriate controls so as not to have a negative impact on workers’ health. The purpose of this study was to analyze the hazards and their impacts on workers’ health through hazard identification measures, exposure assessments, risk assessments and control recommendations. Methods: Health Risk Assessment of physical and chemical hazards in the Painting Area was undertaken using a semi-quantitative method by calculating a risk assessment matrix using the guidelines from IPIECA & OGP in 2016. Results: Physical hazards were found in the form of lighting hazards, vibrations (arm vibration and whole body vibration), noise and heat pressure. Meanwhile, chemical hazards were found in the form of thinner vapor, solvent, NaNO3, H2SO4, NaOH, H3NSO4 and indoor air quality (CO, NO2, SO2, H2S). The results of the risk assessment matrix obtained 4 levels of risk hazards, consisting of 11.1% in the first priority, 50% in the second priority, 25.9% in the third priority and 12.9% in the condition that did not require immediate action. Conclusion: Physical and chemical health hazards were at 4 levels based on the calculation of risk control priorities. A hierarchy of risk control could be used to reduce the risk of health hazards.Keywords: health risk assessment, ipieca & ogp 2016, painting area, risk assessment matrix